Impact and experiences of vestibular disorders and psychological distress: Qualitative findings from patients, family members and healthcare professionals - Dr Laura J. Smith; Wesley Pyke; Rosanna Fowler; Britta Matthes; Emma deGoederen; Shanmuga Surenthiran (Health Expectations)
Abstract Introduction People with vestibular disorders frequently experience reduced quality of life and challenges with activities of daily living. Anxiety, depression and cognitive problems often co‐present with vestibular disorders and can aggravate symptoms and prolong clinical recovery. We aimed to gain in‐depth insights into the impact of vestibular disorders and the contribution of psychological factors by exploring multistakeholder perspectives. Methods Semistructured interviews were conducted between October 2021 and March 2022 with 47 participants in the United Kingdom including: 20 patients (age M = 50.45 ± 13.75; 15 females), nine family members (age M = 61.0 ± 14.10; four females), and 18 healthcare professionals. Data were analysed using framework analysis. Results Vestibular disorders impact diverse aspects of patients' lives including work, household chores, socialising, and relationships with family and friends. Being unable to engage in valued activities or fulfil social roles contributes to feelings of grief and frustration, affecting identity, confidence, and autonomy. Anxiety and low mood contribute to negative thought processes, avoidance, and social withdrawal, which can impede clinical recovery through reduced activity levels, and end engagement with treatment. Coping strategies were thought to help empower patients to self‐manage their symptoms and regain a sense of control, but these require oversight from healthcare providers. Conclusions Daily activity limitations, social participation restrictions, and psychological distress can interact to impact quality of life, sense of self, and clinical recovery amongst people with vestibular disorders. Information and resources could aid societal awareness of the impact of vestibular disorders and help patients and families feel understood. An individualised and comprehensive approach that concurrently addresses mental, physical, social, and occupational needs is likely to be beneficial. Patient or Public Contribution Two group meetings were held at the beginning and end of the study with a patient and public involvement network formed of people with vestibular disorders and family members. These individuals commented on the study aims, interview schedule, participant recruitment practices, and interpretation of the themes identified. Two core patient members were involved at all stages of the research. These individuals contributed to the formulation of the interview schedule, development and application of the coding scheme, development and interpretation of themes, and preparation of the final manuscript.